2000
DOI: 10.1128/jb.182.9.2428-2437.2000
|View full text |Cite
|
Sign up to set email alerts
|

Calcofluor Antifungal Action Depends on Chitin and a Functional High-Osmolarity Glycerol Response (HOG) Pathway: Evidence for a Physiological Role of the Saccharomyces cerevisiae HOG Pathway under Noninducing Conditions

Abstract: We have isolated several Saccharomyces cerevisiae mutants resistant to calcofluor that contain mutations in the PBS2 or HOG1 genes, which encode the mitogen-activated protein kinase (MAPK) and MAP kinases, respectively, of the high-osmolarity glycerol response (HOG) pathway. We report that blockage of either of the two activation branches of the pathway, namely, SHO1 and SLN1, leads to partial resistance to calcofluor, while simultaneous disruption significantly increases resistance. However, chitin biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 40 publications
7
96
0
4
Order By: Relevance
“…The link between the HOG pathway and cellwall architecture has been reported in both S. cerevisiae (Alonso- Monge et al, 2001;García-Rodriguez et al, 2000;Jiang et al, 1995;Kapteyn et al, 2001) and C. albicans (Alonso-Monge et al, 1999). We describe growth differences between hog1 and pbs2 in the presence of Congo red and calcofluor white.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The link between the HOG pathway and cellwall architecture has been reported in both S. cerevisiae (Alonso- Monge et al, 2001;García-Rodriguez et al, 2000;Jiang et al, 1995;Kapteyn et al, 2001) and C. albicans (Alonso-Monge et al, 1999). We describe growth differences between hog1 and pbs2 in the presence of Congo red and calcofluor white.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the S. cerevisiae phr1 mutant exhibits a higher proportion of chitin and sensitivity to Nikkomycin Z and calcofluor white (Popolo & Vai, 1998), whereas mutants in chitin synthases chs2 and chs8 have less chitin synthase activity and are therefore hypersensitive to calcofluor white (Munro et al, 2003). In S. cerevisiae, mutants defective in the HOG pathway are resistant to calcofluor white, although no differences were detected in chitin synthesis during vegetative growth or during calcofluor treatment (García-Rodriguez et al, 2000). Additionally, overexpression of the PBS2 gene leads to higher b-1,3-glucan synthase activity and resistance to b-1,3-glucanases (Lai et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of PBS2 in maintaining cell wall plasticity through its control over b-glucan synthesis has also been demonstrated (Jiang et al, 1995;Lai et al, 1997). Recently, Garcia-Rodriguez et al (2000) isolated a pbs2 mutant allele that was capable of conferring resistance to calcofluor but sustained full growth at 1.4 M NaCl, suggesting another physiological function of this gene. However, the detailed molecular mechanisms that result in these phenotypes have yet to be worked out.…”
Section: Introductionmentioning
confidence: 93%
“…Earlier studies (Boguslawski and Polazzi, 1987) have shown that S. cerevisiae cells harbouring a mutation in the PBS2 gene are sensitive to polymyxin B, an antibiotic known to damage the integrity of cell membranes (Storm et al, 1977). Recently, it has been observed that S. cerevisiae pbs2 mutants showed altered calcofluor sensitivity (Garcia-Rodriguez et al, 2000). In such a scenario, it was interesting to see whether DPBS2 could complement these phenotypes in the S. cerevisiae pbs2 mutant.…”
Section: Sequence Analysis Of the Dpbs2 Genementioning
confidence: 99%